2020
DOI: 10.1111/are.14578
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus sequence typing (MLST) analysis of California Flavobacterium psychrophilum reveals novel genotypes and predominance of CC‐ST10 in California salmonid hatcheries

Abstract: Flavobacterium psychrophilum is a psychrophilic, Gram-negative bacillus and the aetiologic agent of bacterial coldwater disease (BCWD) and rainbow trout fry syndrome (RTFS;Madetoja, Hänninen, Hirvelä-Koski, Dalsgaard, & Wiklund, 2001). Clinical signs of F. psychrophilum infection, as well as mortality rate, are largely dependent on multiple factors including fish size, age and host immunity (Holt, 1993;Starliper, 2011). Disease typically occurs at water temperatures between 10°C and 14°C (Borg, 1960), with cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…Isolates recovered from China fell into five distinct STs, with most (i.e., 23/31) belonging to three novel MLST singleton STs that are distinct from the >1,500 isolates that have been genotyped using the scheme of Nicolas et al ( 11 ) and originated from five different continents ( 10 , 12 , 13 , 31 36 ). Among the three newly discovered singletons, one (e.g., ST355) contained isolates that were recovered exclusively from one host species (e.g., rainbow trout), whereas ST356 and ST357 were recovered from two salmonid species belonging to two different genera (e.g., Salvelinus and Oncorhynchus ) ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolates recovered from China fell into five distinct STs, with most (i.e., 23/31) belonging to three novel MLST singleton STs that are distinct from the >1,500 isolates that have been genotyped using the scheme of Nicolas et al ( 11 ) and originated from five different continents ( 10 , 12 , 13 , 31 36 ). Among the three newly discovered singletons, one (e.g., ST355) contained isolates that were recovered exclusively from one host species (e.g., rainbow trout), whereas ST356 and ST357 were recovered from two salmonid species belonging to two different genera (e.g., Salvelinus and Oncorhynchus ) ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping via MLST also revealed that isolates belonging to CC-ST10, the largest and by far most globally widespread F. psychrophilum clonal complex that has a strong proclivity for rainbow trout ( 9 13 , 34 , 36 ), are also present in China ( Table 2 ). In fact, the two CC-ST10 STs that were detected in China (e.g., ST12 and ST78) are single-locus variants (SLVs) of one of the largest currently recognized F. psychrophilum STs (e.g., ST10) ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, subclinical, or asymptomatic infection in which an individual is infected but does not show overt signs of disease cannot be ruled out without conventional diagnostic testing. F. psychrophilum is endemic to California, including the estuary, and causes bacterial coldwater disease in salmonids, namely Rainbow Trout, as well as in other non-salmonid fishes (reviewed in Starliper 2011; Sebastião et al 2020). Similarly, C. shasta and P. minibicornis are myxosporean parasites of the digestive tract and kidneys, respectively, that are known to be present and infect salmonids throughout the estuary and its tributaries year-round (Lehman et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…2019; Sebastião et al. 2020). Empirical observations from field studies suggest that isolates belonging to some CCs differ in host species preference (Nicolas et al.…”
mentioning
confidence: 99%
“…Flavobacterium psychrophilum, the causative agent of bacterial coldwater disease (BCWD; Borg 1948), generates heavy losses in farmed Rainbow Trout Oncorhynchus mykiss worldwide (reviewed in Loch and Faisal 2017). Multilocus sequence typing has revealed substantial global F. psychrophilum genetic diversity, with at least 320 sequence types (STs) clustered in 31 clonal complexes (CCs; Nicolas et al 2008;Fujiwara-Nagata et al 2013;Nilsen et al 2014;Knupp et al 2019;Sebastião et al 2020). Empirical observations from field studies suggest that isolates belonging to some CCs differ in host species preference (Nicolas et al 2008;Van Vliet et al 2016;Knupp et al 2019), virulence (Nilsen et al 2014;Van Vliet et al 2016;Knupp et al 2019), serotype Rochat et al 2017), and frequency of association with disease outbreaks (Nilsen et al 2014;Van Vliet et al 2016;Knupp et al 2019).…”
mentioning
confidence: 99%